Performance investigation of publish/subscribe approach for data dissemination in opportunistic networks - Lenando, Halikul; Albert, Sanjay Charles; Jambli, Mohamad Nazim; Abdullah, Johari (2016)
Nowadays, disseminating information over the networks is effortless as most of the smart devices i.e.smartphone are connected to the Internet.The development of new applications also contribute to the rapid grows of data over the Internet.Internet Service Provider (ISP) claims that currently more than 50% of the traffic is generated by Peer to Peer (P2P) applications such as file-sharing, distributed computing, internet-based telephony and etcetera.P2P is selforganizing system and autonomous which can be used to as a communication medium to disseminate information at the rural area.In this paper, we proposed Publish/Subscribe system as a way of disseminating information in opportunistic network.This technique can be used to disseminate information in the rural area as the nature of the network in the rural area has the same characteristics as opportunistic networks i.e. Intermittent and unstable network connectivity.From the simulation results, we found that the new way of deploying Publish/Subscribe approach that we proposed in this paper i.e. Publish without Limit (PWL) and Publish upon Request (PUR) manage to reduce the overheads while maintaining the performance as better as Epidemic approach.This approach has opportunity to create effective communication in the rural area.